Most frequent injuries in Cuban weightlifters. main causes and prevention measures (Original) (Revista científica Olimpia, 2020)
Weightlifting, sport emerged in the XIX century from one of the natural activities that the men most realize from remote times: the lift and transport of different loads, is, at present, an inclusive sport for both sexes, with potentiality to sum a substantial number of medals in multisport events at different levels. In Cuba, his practice begins from early ages (11-12 years) until arrive at high performance in junior and adults categories. Nevertheless been a sport that had attributed negative effects, is one of the physical exercises with lesser incidence of lesions. The investigation had as objective to identify the more frequent lesions in a sample of different categories Cuban weightlifters (n = 88), as just as the factors that predisposed and to propose some rules for his prevention.
Keywords: weightlifting; injuries